The dorsolateral prefrontal network is involved in pain perception in knee osteoarthritis patients - Hiramatsu, Takeshi; Nakanishi, Kazuyoshi; Yoshimura, Shinpei; Yoshino, Atsuo; Adachi, Nobuo; Okamoto, Yasumasa; Yamawaki, Shigeto; Ochi, Mitsuo (Neuroscience letters, 2014)
•Dorsolateral prefrontal cortex (DLPFC) activity increases significantly in knee OA.•DLPFC activity is associated with activity in the pain matrix in controls.•DLPFC activity increases without association with pain matrix activity in OA.•Chronic pain induces abnormal brain connectivity between DLPFC and pain matrix. Functional MRI (fMRI) studies have been used to investigate how the brain processes noxious stimuli in osteoarthritis (OA) and to identify the cortical location of pain perception. However, no consensus has been reached regarding brain activity associated with pain-induced conditions in OA patients. We examined cerebral responses using intra-epidermal electrical stimulation of the . knee in knee OA patients. To replicate the pain of knee OA in terms of predictability, acute pain generated by electrical stimulation was provided simultaneously with displayed images in this study. We used fMRI to identify differences in response between healthy subjects and knee OA patients and explored the modulating cortico-subcortical and cortico-cortical pathways using psychophysiological interaction (PPI) analysis. Our results show that chronic pain results in a different brain activation profile in the DLPFC and the pain matrix in knee OA patients. Abnormal brain connectivity between the DLPFC and the pain matrix is induced by chronic pain in knee OA patients.